2015
DOI: 10.1007/s12262-015-1291-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heparanase and VEGF-C mRNA Expressions in Lung Cancer

Abstract: The objective of this study is to investigate relationship between the expressions of heparanase and vascular endothelial growth factor-C (VEGF-C) mRNA and tumorigenesis, progression in human lung cancer. The expressions of heparanase and VEGF-C mRNA in 65 cases of lung cancer (31 cases of squamous cell carcinoma, 25 adenocarcinoma, 3 large cell carcinoma, and 6 small cell carcinoma), adjacent tissues of cancer, and normal tissues were tested by reverse transcription-polymerase chain reaction (RT-PCR) and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These observations mean that the unstable expression of these genes can cause different oncological outcomes. VEGF-C has been widely reported in lung cancer and is involved in lung cancer tumourigenesis and associated with lymphatic metastasis; it can be used as a biomarker for evaluating recurrence and prognosis in non-small cell lung cancer [29]. ANGPTL4 (Tumour cell-derived human angiopoietin-like protein 4) can damage vascular endothelial cell junctions, increase pulmonary capillary permeability, and promote the process of tumour cells protruding through the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…These observations mean that the unstable expression of these genes can cause different oncological outcomes. VEGF-C has been widely reported in lung cancer and is involved in lung cancer tumourigenesis and associated with lymphatic metastasis; it can be used as a biomarker for evaluating recurrence and prognosis in non-small cell lung cancer [29]. ANGPTL4 (Tumour cell-derived human angiopoietin-like protein 4) can damage vascular endothelial cell junctions, increase pulmonary capillary permeability, and promote the process of tumour cells protruding through the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, VEGF-C protein expression does not appear to significantly relate to LUAD patient survival. Yang et al found that VEGF-C mRNA expression correlated with survival of the patients with lung cancer [ 7 ]. The biological functions of VEGF-C may be analyzed as a potential prognosis factor in LUAD.…”
Section: Introductionmentioning
confidence: 99%